Measuring Statistical Evidence Using Relative Belief - Evans, Michael (Chapman and Hall/CRC, 2015)
A Sound Basis for the Theory of Statistical InferenceMeasuring Statistical Evidence Using Relative Belief provides an overview of recent work on developing a theory of statistical inference based on measuring statistical evidence. It shows that being explicit about how to measure statistical evidence allows you to answer the basic question of when.